Grade 10 life sciences learners' views on the intergration of indigenous knowledge-related topics using a cooperative learning approach - Sefoka, Thabelang Segopotse (My University, 2024)
The focus of this study was to explore Grade 10 Life Sciences learners’ views on the integration of indigenous knowledge-related topics using a cooperative learning approach. The study was underpinned by social constructivism theory, whereby a qualitative single-case study design was used. Eight Grade 10 Life Sciences learners from a school in Moroke Circuit, Sekhukhune East District, Limpopo Province, participated in the study. Document reviews, observations (participation observer), and focus group interviews were used to collect data. Additionally, data was analysed using categorical aggregation, and an inductive approach was also used. The findings of this study revealed that the adapted teaching methods under the cooperative learning approach, the jigsaw and De Bono’s thinking hats, are efficacious in integrating indigenous knowledge (IK) in the Life Sciences (LFSC) classroom. These methods enabled learners to engage in constructive dialogues that required each of them to bring out and relate to their IK related to the LFSC topics. This has caused the IK that is held by each individual to be easily accessible and used in the classroom. As such, the IK that has emanated from the learning groups has allowed the teacher and the learners to learn and acquire important knowledge from each other. Additionally, these learning methods have developed and enhanced important 21st century skills in the learners, which include critical thinking, social, and interpersonal skills. The findings further revealed that the integration of IK in LFSC classrooms improved participation, learning, and comprehension of LFSC topics. IK served as the prior knowledge through which teaching and learning were based and enabled the use of vernacular language. It also allowed learners to see the relationship between LFSC topics and their IK, resulting in more meaningful and enhanced learning. Hence, they advocate for learning all their school subjects this way. Furthermore, it allowed the teacher to draw out important IK from the learners that can be used in the LFSC classroom, such as indigenous medicines, nutrition, traditional technology, and skills Interestingly, this study has revealed that when learners are given space and a voice, they are able to express critical, confident, and independent views from which teachers can draw a lot. Therefore, the study recommended that teachers create learning contexts that allow learners to talk about their IK. Hence, a cooperative learning approach is recommended for such a space.
Thesis (M. Ed. (Science Education)) -- University of Limpopo, 2024
Keywords: Indigenous knowledge; Cooperative learning; Life Sciences; Social Constructivism; Traditional ecological knowledge; Group work in education; Life sciences; Education -- Curricula